Effect of fluoride on photosynthetic pigment content and antioxidant system of Hydrilla verticillata. Issue 12 (15th October 2018) - Gao, Jingqing; Liu, Chun; Zhang, Jingshen; Zhu, Songfeng; Shen, Yu; Zhang, Ruiqin
ABSTRACT: Fluoride can either inhibit or enhance the growth of aquatic macrophytes, depending upon fluoride concentration and exposure time. To investigate fluoride toxicity, the submerged plant Hydrilla verticillata was treated with various concentrations of fluoride (F) (0, 10, 20, and 40 mg/L) for different lengths of time (7, 14, 21, and 28 days). At exposure to 10 mg/L F, the content of chlorophyll, protein, and carbohydrates content increased in leaves of H. verticillata, and the activity of guaiacol peroxidase (POD) and superoxide dismutase (SOD) slightly increased in plants compared with the control. When fluoride concentration increased to 20 mg/L, the toxic effect generated by fluoride led to a reduction of chlorophyll, protein, and carbohydrates in H. verticillata, but the activity of guaiacol peroxidase and SOD and the amount of ascorbic acid (AsA) and glutathione (GSH) were enhanced significantly. After exposure to fluoride at 40 mg/L for a long period, these physiological parameters showed a sharp decrease, and inactivation was observed in H. verticillata . These results suggested that a certain concentration of fluoride induced antioxidant response, and excess fluoride induced metabolism imbalance and oxidative damage in H. verticillata .